La novela como espacio de posibilidad. Memorias subalternas en la obra de Juan Marsé - Ángela Martínez Fernández (Mélanges de la Casa de Velázquez)
This article proposes an analysis of Juan Marsé’s work based on the theme of memory. In order to do so, we start by differentiating between the diverse processes concerning memory and we find that in the author’s fictional project the so-called “subaltern memory” takes on special relevance. The protagonists, Charnegos from the Catalan periphery, and their use of popular tradition (through cinema and aventis) run uninterruptedly through Juan Marsé’s narrative and are placed at the service of a literary truth that functions in opposition of the truth imposed by the Franco regime. The aim is to detect not only what kind of memories proliferate in Marsé’s narrative, but also what political sense they have in relation to the dictatorial past; that is, how the subaltern memories of the Kabileños construct in fiction a universe of reference different from that imposed by official memory.